Las TIC como herramientas en el proceso educativo en el subnivel elemental para los docentes de la Unidad Educativa “19 de Septiembre” durante el periodo académico 2021-2022. - Zapata Pilatasig, Mayra Alexandra (2022)
This research work addresses a problem related to the use and management of ICT by teachers; for which it has been proposed as a general objective to apply ICT in the teaching-learning process of teachers of the elementary sublevel of the Educational Unit "19 de Septiembre". To achieve the stated objective, a quantitative and qualitative approach was used as a methodology, that is, mixed because aspects related to the use and management of ICT in the teaching-learning process were evaluated; the research is of an applied type because it allows the transformation of reality in the educational institution. For data collection, the survey technique was applied and the questionnaire as an instrument, when identifying the analysis of the results obtained, it is concluded that teachers have low knowledge about the use and management of the Jamboard blackboard and virtual platforms such as Genially and Educaplay , for which it was pertinent to address topics of interest such as definitions, advantages, use and management of blackboards and virtual platforms, thus being these digital tools attractive to students, which allowed greater interaction and collaboration between teacher - student. The proposal to design a manual with the help of workshops and tutorial videos for teachers of technological tools was proposed, which was validated by specialists and users, teachers were encouraged to update their knowledge in the use and management of ICT.